SEMANTIC ANALYSIS OF ADVANCED VOCABULARY RELATED TO WORK AND TIME - Karimquliyeva Gulhayo Hikmat qizi (Bright Mind Publishing, 2026)
This study investigates the lexical challenges faced by advanced English learners in Uzbekistan, focusing on a specific unit of a widely used textbook for professional and academic communication. The research examines over 500 lexical items, including phrasal verbs, idioms, collocations, and word formations, and categorizes them according to their semantic and functional characteristics. Findings indicate that many expressions are highly context-dependent and culturally nuanced, making translation or literal understanding difficult. The study highlights the need for context-rich teaching strategies, practical examples, and communicative activities to facilitate effective learning. Recommendations for educators and suggestions for future research are provided to enhance learners’ competence and confidence in using complex English expressions in real-life and professional contexts.
Keywords: lexical challenges, idiomatic expressions, advanced learners, contextual learning, professional communication, language acquisition